Effect of Venous Occlusion on Coagulation and Fibrinolytic Components in Normal Subjects - Nilsson, Inga Marie; Robertson, B (Thrombosis and Haemostasis, 1968)
The components of the coagulation and fibrinolytic systems were studied before and during venous occlusion for 20 min of the arm and of the leg in 30 healthy volunteers. For comparison total serum proteins, α2-macroglobulin and albumin were also determined. The values recorded after venous occlusion were corrected according to the changes in the haematocrit.The fibrinolytic activity induced by venous occlusion was markedly higher (4 to 6 times) in the arms than in the legs. In 2 of the subjects, however, venous occlusion was not followed by any increase of fibrinolysis.After venous occlusion total serum proteins increased by 15% but albumin only by 2%. The P & P, AHF, haemophilia B-factor and fibrinogen increased by 5-20%. The factor V-level remained unchanged. The AHF and factors XI and XII increased by about 20% in the legs but by about 40% in the arms. In other respects the upper and lower limbs showed the same type of coagulation changes.The plasminogen level increased in both arms and legs by 10%. The inhibitors of urokinase activation and the α2M remained unchanged, which means that these inhibitors compared with the increase in total serum proteins had decreased by about 10%.The 2 normals, in whom venous occlusion failed to produce any increase of fibrinolysis, had no signs of Hageman trait and after venous stasis the same coagulation changes occurred as in the individuals who developed high fibrinolytic activity.The findings argue against the Hageman factor playing an essential role in the activation of the fibrinolytic system during venous occlusion and indicate that the increase in fibrinolysis is due to release of activators from the vessel walls.